Numerical simulation of tooth extraction socket: alveolar bone regeneration. Issue 1 (May 2021) - Furukawa, Rintaro; Nagayama, Katsuya; Matsuo, Masato
Abstract: Recently, regenerative medicine has received attention owing to the progress of an aging society. Regenerative dentistry, such as bone regenerative therapy and implant treatment to regain bone loss as a result of active periodontal disease, is actively performed. The alveolar bone is a functional bone that supports teeth and buffers occlusal pressure. In the implant treatment, the implant is inserted into the tooth after it has been extracted. After the implant is inserted, the alveolar bone will regenerate over about three months and the implant will be fixed in place. During this process of alveolar bone regeneration, there have been problems with the implant and alveolar bone not bonding. This work was contributed to dental regenerative medicine by building a simulation model of alveolar bone regeneration. After tooth extraction is performed, the alveolar bone regenerates by chemically converting calcium (Ca) secreted from the newly formed blood vessels into hydroxyapatite, which is the main component of bone. Thus, its internal structure and external shape are mechanically affected around the bone. The main purpose of this study is to establish a mathematical model, introduced as the Ca transport model that is secreted from the newly formed blood vessels, and mechanical factor model expressed as bone remodeling for analyzing and predicting the interaction of angiogenesis and bone regeneration. As a result, we were able to obtain a good agreement between the qualitative features of the experimental images and the simulation results.